Prevalence of Empyema, Mucocele, Strawberry Gallbladder and Carcinoma in Patients Undergoing Cholecystectomy with Diagnosis of Chronic Cholecystitis - Khomusi , Munira Murtaza; Parveen , Sughra; Iqbal , Mazhar; Ahmed , Tanweer; Husain , Razia; Seth , Uzma Shamim; Soomro , Jehangir Ali; Khan , Zainab Sariyah (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
The objective of this chapter was to find out the prevalence of mucocele or empyema in chronic cholecystitis using cholecystectomy findings and histopathological reports. Cholecystitis is the sudden inflammation of gallbladder. If this condition persists over time, such as for months, with repeated attacks, or if there are recurrent problems with gallbladder function, it’s known as chronic cholecystitis. This observational cross-sectional study was conducted in Surgical Ward 1, Jinnah Postgraduate Medical Center from December 2019 to December 2021 for two years. Patients who were diagnosed with acute cholecystitis, mucocele, or empyema on clinical examination and ultrasonography were excluded from the study. The laparoscopic cholecystectomy was performed, and the surgical results were recorded. Gall bladder samples were sent for histology after being checked for mucocele and empyema. Chronic cholecystitis is usually due to cholelithiasis but incidentally, other pathologies are found. Chronic cholecystitis is also a risk factor for carcinoma. The finding of mucocele was confirmed on histopathology. Gallbladder was not palpable in this study as compared to the abovementioned study. Cholecystectomy becomes difficult due to impacted stone at cystic duct. It was determined that prolonged cholecystitis could result in empyema, mucocele, and strawberry gall bladder, making cholecystectomy challenging in such circumstances.